Household crowding associated with childhood otitis media hospitalisations in New Zealand - Christopher Bowie; Amber L. Pearson; Malcolm Campbell; Ross Barnett (Elsevier, 2014)
Abstract Objective: To examine the association between hospitalisations for otitis media and area‐level measures of household crowding among children in New Zealand. Methods: Counts of hospital admissions for otitis media by census area unit were offset against population data from the 2006 national census. Area‐level household crowding, exposure to tobacco smoke in the home, equivalised income and individual‐level characteristics age and sex were adjusted for. To examine effect modification by ethnicity, three separate poisson models were examined for the total, Māori and non‐Māori populations. Results: Household crowding was significantly associated with hospital admissions for otitis media after adjustment in all three models. Neighbourhoods with the highest compared to the lowest proportion of crowded homes exhibited incidence rate ratios of 1.25 (95%CI 1.12-1.37) in the total population, 1.59 (95%CI 1.21-2.04) in the Māori restricted model and 1.17 (95%CI 1.06-1.32) in the non‐Māori restricted model. Conclusions: Otitis media hospitalisations are associated with area‐level measures of household crowding and other risk factors in this ecological study. The largest increase in otitis media incidence relative to neighbourhood rates of household crowding was exhibited among Māori cases of otitis media. Implications: This study adds weight to the growing body of literature linking infectious disease risk to overcrowding in the home.